РАССКАЗЫ И ДРАБЛЫ В УЗБЕКСКОЙ ЛИТЕРАТУРЕ (Scientific journal of the Fergana State University, 2024)
The article examines the emergence and development of storytelling in Uzbek literature, the writers who created the story in this genre, their work to the present day. In addition, the role of the drabble in Uzbek literature is analyzed.